A prospective study of 39 patients with trigeminal neuralgia treated with percutaneous balloon compression - Wuilker Knoner Campos; Marcelo N. Linhares (Arquivos de Neuro-Psiquiatria)
OBJECTIVE: Trigeminal neuralgia is the most common facial pain. It may be treated with percutaneous balloon compression (PBC), which is considered to be a safe and efficient procedure. The purpose of this study was to review our results with PBC and to assess the factors influencing the outcome. METHOD: A multivariate analysis was used to study 39 patients during a 50-month postoperative period. RESULTS: There was predominance of the female gender (54%), the right side of the face (84%) and V2V3 roots of trigeminal nerve (33%). The mean age was 62.3 years. No major complications or deaths occurred. Among all variables, postoperative hypoesthesia was the single prognostic factor capable of positively influencing the results (p=0.02). Most patients (80%) were pain-free after 50 months with a 90% satisfaction rate. CONCLUSION: PBC was a safe procedure with low morbidity, no mortality, high approval ratings, and was an important improving on patients' quality of life.